Prevalence of Gastrointestinal Nematode of Sheep in Mosul and Erbil City - Manal himmadi hasan; waad khalid Khalaf; maan tahir Jarjees (مجلة الانبار للعلوم البيطرية)
This study was designed to explore and assess the status of nematode infection of sheep based on the prevalence, identification genera and species of detected eggs, age and sex of infected sheep, type of infection (single, double, mixed), type of sheep breeding (outdoor/indoor husbandry) and intensity of infection (light, moderate, heavy). One hundred and eighty-five fecal samples were microscopically examined which were randomly collected from different locations of Mosul and Erbil cities. The sheep of the study were of different ages and both sexes and were carried out during the period from January until the December 2020. Conventional helminthic examination methods were applied including the examination and description of genera and species of the egg worms. The findings indicated that the total infection rate was 46.49%. In all sheep of both areas, the highest infection rates were observed in adults and older sheep (2-3 years and >3 years). There was no significant difference between infection rates of males and females. It was found that "light" type of intensity of infection (50-800) egg/g was the most predominant in both sheep representing 63.6% and 59.5% of Mosul and Erbil cities, respectively. It can be conducted that the infection with a single type of nematodes was generally prevalent in the examined sheep of the two cities .According to the degree of infection concomitant to the management of housing, indoor type of breeding is better that outdoor type of Mosul sheep, while the outdoor type of had the worse influence in Erbil sheep city. Although, the predominant type of intensity of infection was light (50-800 egg/g ) among all sheep investigated, those sheep need to be regularly and continuously administered with effective and suitable anthelmintics.